1986
DOI: 10.1152/ajprenal.1986.250.5.f907
|View full text |Cite
|
Sign up to set email alerts
|

Renal escape from vasopressin: role of pressure diuresis

Abstract: This study was designed to examine the role of increased renal artery pressure (RAP) in mediating escape from the antidiuretic action of vasopressin (AVP). In six conscious dogs in which RAP was permitted to increase, AVP infusion, at a rate (0.2 mU X kg-1 X mm-1 iv) that was acutely subpressor, gradually raised mean arterial pressure (MAP) from 97 +/- 2 to 126 +/- 4 mmHg after 5 days while decreasing urine volume and increasing urine osmolality. However, after 4-5 days of AVP infusion, urine volume and osmola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…16,17 Although vasopressin and norepinephrine are powerful peripheral vasoconstrictors, they usually cause only small increases in blood pressure when chronically infused, as long as kidney function is not markedly impaired. 16,17 That these potent vasoconstrictors cause only mild hypertension, even though they initially elicit large increases in vascular resistance and blood pressure during acute infusions, is difficult to explain if one considers that increased peripheral vascular resistance is the primary cause of hypertension. However, the failure of vasopressin or norepinephrine to cause sustained, severe hypertension is understandable if one considers the fact that they also have relatively weak antinatriuretic actions.…”
Section: Servo-control Of Renal Perfusion Pressure In "Vasoconstrictomentioning
confidence: 99%
“…16,17 Although vasopressin and norepinephrine are powerful peripheral vasoconstrictors, they usually cause only small increases in blood pressure when chronically infused, as long as kidney function is not markedly impaired. 16,17 That these potent vasoconstrictors cause only mild hypertension, even though they initially elicit large increases in vascular resistance and blood pressure during acute infusions, is difficult to explain if one considers that increased peripheral vascular resistance is the primary cause of hypertension. However, the failure of vasopressin or norepinephrine to cause sustained, severe hypertension is understandable if one considers the fact that they also have relatively weak antinatriuretic actions.…”
Section: Servo-control Of Renal Perfusion Pressure In "Vasoconstrictomentioning
confidence: 99%
“…5 Recently, Chou et al 17 have shown that AVP-enhanced water permeability in IM- 18 -20 and increased renal perfusion pressure. 21 The escape is also associated with an increase in renal prostaglandins, 19 a decrease in vasopressin receptors, 22 and a decrease in aquaporin water channels. 23 The present study reveals another pathway whereby AVP can affect IMCDs by increasing intracellular Ca 2ϩ and activating NOS and NO production.…”
Section: Second Pathway For Avp Signal Transduction In Imcdsmentioning
confidence: 99%
“…Chief among these is the phenomenon of renal escape from antidiuresis. In animal models of sustained AVP administration and in patients with the syndrome of inappropriate antidiuretic hormone secretion (SIADH), water loading typically results in free water retention and progressive hyponatremia for several days, which is then followed by escape from the AVP-induced antidiuresis (4,16). With the onset of vasopressin escape, water excretion increases despite sustained administration of AVP, allowing water balance to be reestablished and the serum [Na ϩ ] to be stabilized at a steady, albeit decreased level.…”
mentioning
confidence: 99%